Top managers and problems of managing organizations - V. G. Antonov; E. V. Kuptsova; E. S. Kuptsova (Управление)
The article investigates the problem of the management crisis caused by the low efficiency of management personnel in the conditions of economic crisis. The system of management methods is dominated by administrative methods to the detriment of economic and socio-psychological ones. The purpose of the study is to find ways to solve the crisis and improve the efficiency of management personnel. The objectives of the research are to develop approaches to the professional development of personnel and the transformation of the system of labor relations based on the principles of trust management. The study of agency conflict in the management system of organizations was carried out on the basis of desk research, surveys of managers and employees of the management system. The tactical and strategic solutions to improve the management system in organizations have been proposed. The authors conclude that the risk of causing the greatest damage to the management system is associated with the problem of trust. The main principle of management should be the trust of the staff to their managers and their integration into management processes at least at the level of management of the main production business processes. The study reveals the lack of growth of social skills of managers, for whom employees are not partners, but employees-opportunists. According to the authors, it is necessary to unite employees, give them a common goal and make them members of a single team.